The stress distribution in the joints of vehicles chassis frames subject to torsion - Alvi, M. S. I. (Cranfield University, 1978)
The problem of warping inhibition in the joints, of commercial vehicle chassis frames is very important for the estimation. of stress distribution in the joints and the overall torsional stiffness of frames. The joints being the weakest parts in the entire frame require that the stress levels should be estimated when designing a frame for required torsional stiffness. Plate theory has been applied to-analyse stress distributions in the joints of a ladder frame-in torsion. The frame consists of channel section cross members-welded to the web: of the side members. The degree of cross member warping inhibition in the welded joints has also been estimated analytically by using the concept of the strip beam theory. - The analytical values of stresses have been compared with-photoelastic measurements on photoelastic models of isolated joints and a complete ladder frame.